The universe works on a math equation that never even ever really even ends in the end: Charles Sanders Peirce's Evolutionary Metaphysics and the Law of Large Numbers - Jarrott, Joshua, author; Kasser, Jeff, advisor; Gorin, Moti, committee member; Beachy-Quick, Dan, committee member (Colorado State University. Libraries, 2018)
Recent work on Charles Sanders Peirce's evolutionary cosmology and scientific metaphysics has revealed a tension between two accounts Peirce gives of the laws of nature. Andrew Reynolds points out that Peirce seems to have thought that the laws evolved both in a statistical way—according to which the laws themselves are the statistical result of the Law of Large Numbers applied to instances of the laws—and also in a more directly evolutionary way, according to which instances of the laws reinforce one another making future instances conform to past ones. By forming "habits". These two analyses are straightforwardly incompatible, since the Law of Large Numbers requires events in the series to which the statistical analysis applies to be independent from one another, whereas the other account explicitly involves future law instantiations depending on past ones. Reynolds calls this problem the Incompatibility Problem. Despite the apparent contradiction, the work of this paper attempts a rational reconstruction of Peirce's evolutionary metaphysics, and on this reinterpretation of Peirce's cosmology, the incompatibility problem does not arise. On this view, the laws of nature remain statistical results of chance property instantiations, including dispositional property instantiations. It is argued, however, that Peirce need not be committed to the idea that instantiations of laws are dependent on one another. Rather, the view according to which habits in nature are formed is argued to apply to properties of the universe as a whole, thereby explaining why the universe contains any regularities at all. The so called "law of habit" is shown to be a special case of the Law of Large Numbers as applied to the world's properties, and the laws of nature are shown to be statistical results of various property instantiations.
Keywords: history of philosophy; metaphysics; pragmatism; Law of Large Numbers; Peirce; American philosophy